Issue Information TOC. Issue 1 (5th March 2019) - Unknown
Abstract : Cover : In Kasprick et al. (https://doi.org/10.1002/cpph.55 ), the image shows analysis of skin sections. (A) Determination of titer from rabbits immunized with mCOL7 vWFA2 . Cryosections of normal mouse skin were incubated with serum diluted 1:4, 000 1:8, 000, 1:16, 000, and 1:32, 000 and then stained with FITC‐AffiniPure donkey anti‐rabbit IgG as described in Basic Protocol 3. As the serum specifically binds to the dermal‐epidermal junction of the skin, a typical green line is visible (arrows). The line visible at the lowest tested concentration determines the titer (here, 1:8, 000). (B) Analysis of H&E staining. Typical ear sections 12 days after first IgG injection in antibody transfer–induced EBA. Upper left picture shows a mild inflammation with less thickening and only a few inflammatory cells. Other pictures show typical thickening of the epidermal layers and massive inflammation. Arrows indicate split formation at dermal‐epidermal junction; ** indicates cartilage of the ear.